The immune system and stroke: from current targets to future therapy. Issue 1 (10th August 2018) - Malone, Kyle; Amu, Sylvie; Moore, Anne C; Waeber, Christian
Abstract: Stroke is a major cause of morbidity and mortality worldwide. Despite the intensive search for new therapies, hundreds of agents targeting various pathophysiological mechanisms have failed clinical trials, and the thrombolytic agent tissue plasminogen activator is currently the only FDA‐approved medication for the treatment of acute ischemic stroke. The immune system is involved in all stages of stroke, from the pathogenesis of risk factors to neurotoxicity, to tissue remodeling and repair. There is a bidirectional interaction between the brain and the immune system, with stroke‐induced immunosuppression and subsequent infection a principal source of patient mortality. Newer work also points to a role for the gut microbiota in the immune response to stroke, while clinical sequelae such as dementia might now also be explained in immune terms. However, the exact roles of innate and adaptive components have not been fully elucidated, with studies reporting both detrimental and beneficial functions. Time is a key determinant in defining whether immunity and inflammation are neuroprotective or neurotoxic. The local inflammatory milieu also has a clear influence on many proposed treatments. This review examines the individual components of the immune response to stroke, highlighting the most promising future stroke immunotherapies. Abstract : Acute ischemic stroke is a major cause of morbidity and mortality worldwide, and yet the thrombolytic agent tissue plasminogen activator is currently the only FDA‐approved medication. The immune system is involved in all stages of stroke, from the pathogenesis of risk factors to neurotoxicity, to tissue remodeling and repair. This review examines the individual components of the immune response to stroke, highlighting the most promising future stroke immunotherapies.